Pengaruh Larutan Mikroorganisme Lokal Dari Limbah Pisang Terhadap Pertumbuhan dan Hasil Tanaman Buncis (Phaseolus vulgaris L.) - Agusty Saputra; Revi Nurjunika Sari; Alvera Prihatini Dewi Nazari; Ellok Dwi Sulichantini (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2025)
ABSTRACT Green beans (Phaseolus vulgaris L.) are high potential leguminous crops whose productivity can be enhanced through the use of local microorganism (MOL) solutions derived from banana waste. This study evaluated the effects of MOL solutions from banana corm, stem, and peel on green bean growth and yield. The experiment was arranged in a Randomized Block Design (RBD) with four treatments and ten replications. Data were analyzed using analysis of variance (ANOVA), and significant differences were further examined using the Least Significant Difference (LSD) test at 5% significance. Results showed that all MOL treatments significantly increased the number of pods per plant, while other growth parameters including plant height, number of branches, flowering and harvest age, pod length, and fresh pod weight were not significantly affected. Among the treatments, the MOL solution from banana peel was the most effective, demonstrating its potential as an organic biofertilizer for improving green bean yield.Keywords : banana, beans, local microorganism solutions.